2011
DOI: 10.4025/actasciagron.v33i4.6664
|View full text |Cite
|
Sign up to set email alerts
|

Time distribution of heavy rainfall events in Urussanga, Santa Catarina State, Brazil

Abstract: ABSTRACT.A knowledge of rainfall time distribution is important for several types of hydrological studies related to surface runoff. This study aims to determine the time distribution pattern of heavy rain events in Urussanga, Santa Catarina State, Brazil. It employed recording rainfall charts from the meteorological station of Urussanga (latitude: 28.31° S, longitude: 49.19° W, altitude: 49 m) from 1980 to 2007. Rain events were classified into four types according to the duration quartile in which the greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 12 publications
2
19
0
12
Order By: Relevance
“…up to 64%, 54% and 49% in AEB, CEB, and GEB, respectively. This is in accordance with Back (2011), which showed that in Brazil the rainfall events tend to concentrate their rainfall depths mainly in the first and second quartiles. The presence of R-events after the reclassification in GEB typifies the slight and uniform rainfall event commonly found in shallow convective clouds, which occur more frequently over the ocean and coastal areas from March to August in tropical Northeast region of Brazil (BRINGI et al, 2003;DILMI et al, 2016;PALHARINI;VILA, 2017;TEIXEIRA, 2008).…”
Section: Hyetograph Type Proportions Before and After The Sl-events Rsupporting
confidence: 91%
See 1 more Smart Citation
“…up to 64%, 54% and 49% in AEB, CEB, and GEB, respectively. This is in accordance with Back (2011), which showed that in Brazil the rainfall events tend to concentrate their rainfall depths mainly in the first and second quartiles. The presence of R-events after the reclassification in GEB typifies the slight and uniform rainfall event commonly found in shallow convective clouds, which occur more frequently over the ocean and coastal areas from March to August in tropical Northeast region of Brazil (BRINGI et al, 2003;DILMI et al, 2016;PALHARINI;VILA, 2017;TEIXEIRA, 2008).…”
Section: Hyetograph Type Proportions Before and After The Sl-events Rsupporting
confidence: 91%
“…Changes in rainfall distribution affect the highest fraction positively and the lowest fraction of individual storms negatively, especially under higher temperatures (WASKO; SHARMA, 2015). Also, Back (2011) showed that rainfall events concentred in the first and second hyetograph quartiles are more frequent along summer season in the tropical wet regions of Brazil. As a result, a unimodal (triangular) hyetograph type influences the time-to-peak and shape of runoff hydrographs (BALL, 1994); meanwhile, a rectangular hyetograph affects the infiltration and runoff generation processes (DUNKERLEY, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Further procedural details can be found in Huff (1967) and Bonta (2004). Huff quartiles are widely used in the analysis of rainfall event profiles (Azli and Rao, 2010;Back, 2011;Bonnin et al, 2006;Bonta and Shahalam, 2003;Powell et al, 2007;Sharafati and Zahabiyoun, 2013;Vandenberghe et al, 2010).…”
Section: Field Site and Methodsmentioning
confidence: 99%
“…Essa constatação deve-se em parte ao fato de no verão predominarem as chuvas intensas do tipo convectivo, que são caraterizadas pela curta duração, enquanto no inverno prevalecerem as do tipo frontais, distinguidas pela longa duração. Resultados semelhantes foram obtidos por Back (2011).…”
Section: Methodsunclassified